2
![f(x) = e^x + 3^x\\f'(x) = e^x + \ln(3) \cdot 3^x f(x) = e^x + 3^x\\f'(x) = e^x + \ln(3) \cdot 3^x](https://tex.z-dn.net/?f=f%28x%29%20%3D%20e%5Ex%20%2B%203%5Ex%5C%5Cf%27%28x%29%20%3D%20e%5Ex%20%2B%20%5Cln%283%29%20%5Ccdot%203%5Ex)
![f'(0) = 1 + \ln(3) f'(0) = 1 + \ln(3)](https://tex.z-dn.net/?f=f%27%280%29%20%3D%201%20%2B%20%5Cln%283%29)
4
![y_k = f'(x_0)(x - a) + f(x_0)\\x_0 = 1\\f(x) = e^x + x^4\\f(x_0) = e + 1\\f'(x) = e^x + 4x^3\\f'(x_0) = e + 4\\y_k = (e + 4)(x - 1) + e + 1 = (e + 4)x - 3 y_k = f'(x_0)(x - a) + f(x_0)\\x_0 = 1\\f(x) = e^x + x^4\\f(x_0) = e + 1\\f'(x) = e^x + 4x^3\\f'(x_0) = e + 4\\y_k = (e + 4)(x - 1) + e + 1 = (e + 4)x - 3](https://tex.z-dn.net/?f=y_k%20%3D%20f%27%28x_0%29%28x%20-%20a%29%20%2B%20f%28x_0%29%5C%5Cx_0%20%3D%201%5C%5Cf%28x%29%20%3D%20e%5Ex%20%2B%20x%5E4%5C%5Cf%28x_0%29%20%3D%20e%20%2B%201%5C%5Cf%27%28x%29%20%3D%20e%5Ex%20%2B%204x%5E3%5C%5Cf%27%28x_0%29%20%3D%20e%20%2B%204%5C%5Cy_k%20%3D%20%28e%20%2B%204%29%28x%20-%201%29%20%2B%20e%20%2B%201%20%3D%20%28e%20%2B%204%29x%20-%203)
5
0 \Rightarrow f(x_1) \text{ --- } \mathrm{min}\\" alt="f(x) = x\,3^x\\f'(x) = 3^x + x\ln(3)\,3^x\\f'(x) = 0 \Leftrightarrow 3^x(1 + x\ln(3)) = 0 \Leftrightarrow x_1 = -\frac{1}{\ln(3)}\\f''(x) = \ln(3)\,3^x + \ln(3) (3^x + x\ln(3)\,3^x)\\f''(x_1) > 0 \Rightarrow f(x_1) \text{ --- } \mathrm{min}\\" align="absmiddle" class="latex-formula">
Следовательно, функция убывает на
и возрастает на ![(-\frac{1}{\ln(3)}; +\infty) (-\frac{1}{\ln(3)}; +\infty)](https://tex.z-dn.net/?f=%28-%5Cfrac%7B1%7D%7B%5Cln%283%29%7D%3B%20%2B%5Cinfty%29)